The Global Impact of COVID-19 on the Care of People With Endometriosis - Demetriou, Lysia; Cox, Emma; Lunde, Claire E.; Becker, Christian M.; Invitti, Adriana L.; Martínez-Burgo, Beatriz; Kvaskoff, Marina; Garbutt, Kurtis; Evans, Emma; Fox, Elaine; Zondervan, Krina T.; Vincent, Katy (Frontiers in Global Women's Health, 2021)
Endometriosis is a chronic condition affecting ~10% of women globally. Little is known about the impact of the coronavirus disease 2019 (COVID-19) pandemic on their care. This brief report explores the impact of COVID-19 on the care of people with endometriosis around the world, their priorities in relation to their clinical care during and post the pandemic; and whether they believed endometriosis increases vulnerability to COVID-19. An internet-based survey study collected data in 5 languages between 11th May to 8th June 2020. Only participants with a surgical or radiological diagnosis of endometriosis, aged 18 years or over were included. A total of 6729 eligible respondents completed the survey with 80.7% (95% CI [79.7, 81.6]) reporting a negative impact on their care. This included difficulties obtaining medication (20.3%); cancelled/postponed gynaecology appointments (50.0%); and cancelled/postponed procedures (37.2%). More than half worried that their endometriosis makes them more vulnerable to COVID-19 (54.2%; 95% CI [53.0, 55.4]). Chi-square analysis showed that despite regional variations (p<0.001) the top 3 priorities were consistent around the world: contact with gynaecologists, knowing when procedures would be performed, and mental health support (20.3% prioritising this aspect during the pandemic and 13.0% as restrictions begin to ease). This study shows the substantial impact the COVID-19 pandemic has had on people with endometriosis and describes how they would like care prioritised moving forwards. The findings regarding significant support needs for mental health adds further weight to the growing recognition of attending to such issues as part of good patient centred care.